Pragmatic labeling of a corpus of economic and financial blogs in Spanish - Martínez Egido, José Joaquín (Círculo de Lingüística Aplicada a la Comunicación, 2023)
Economic and financial blogs allow for discourse on economic and financial matters, and can be characterised as a text type which is expository and argumentative in nature, and which facilitates interaction between author and readers. Both parties can use verbal humour as an argumentative discursive strategy, in that they can include in their discourse certain incongruities which demand a humorous interpretation in their resolution, bearing in mind that verbal humour in this textual type is not to be expected, since they are not humorous texts. This study describes the preparation and construction of a set of texts published in Spanish economic and financial blogs, as well as the labelling of these following the guidelines of the GRIALE research group, as a means of making them available on the OBSERVAHUMOR. COM platform to researchers and anyone else with related interests. To this end, a corpus of 21 texts from two economic and financial blogs was created. From these, 100 humorous sequences were selected and the presence of verbal humour in them analysed. A typology of the humorous sequences was established, and the verbal humour therein was then labelled according to the humour markers and indicators detected.
Keywords: Verbal humour; economic and financial Spanish; corpus; blog